The Existence of Equilibrium and the Objective Function of the Firm - David Kelsey; Frank Milne (Queen's University, Department of Economics, 1992)
We consider an economy in which firms' decisions are made by a collective decision of the shareholders. The main result shows that the simultaneous existence of an exchange equilibrium in the market for shares and a voting equilibrium in the internal decisions of firms. We present our results in a general framework, with a measure space of agents. Our framework covers the cases of incomplete markets and externalities between firms and shareholders. We show that a voting rule due to Kramer is a special case.
Keywords: D52; D70; L20; 330; shareholder voting; incomplete markets; sophisticated voting; objective function of the firm